Pollen Shedding and Combining Ability for High Temperature Tolerance in Rice - Mackill, D.J.; Coffman, W.R.; Rutger, J.N. (Wiley, 1982)
High temperature‐induced sterility in rice (Oryza sativa L.) has not been an important problem in traditional cropping patterns. High temperature tolerance will become an important breeding objective as irrigation systems for dry season cropping are developed and rice production in semi‐arid countries expanded. A study was made to ascertain the prospects for breeding heat tolerant cultivars.A diallel cross experiment was conducted in the phytotron at the International Rice Research Institute to determine the combining ability of six rice lines for high temperature tolerance at anthesis. Control plants were kept under a 29/.21C temperature regime. The treated plants were subjected to 38/27 C for 10 days during anthesis. A heat tolerance index was calculated by dividing the percentage of filled grains of the treated plants by that of the control plants. General and specific combining ability effects for this index were highly significant. The tolerant lines, N22, IR2006 and IET4658, had general combining ability effects of 6.80, 4.08 and 3.02, respectively. The susceptible lines, IR28, IR1561 and IR52, had general combining ability effects of —3.40, —4.92 and —5.58, respectively.The amount of pollen shed on the stigma was studied for the six diallel parents and two F~ hybrids under the two temperature regimes (29/21 and 38/27 C). Tolerant cultivars shed more pollen grains on the stigma under both temperature regimes. In the susceptible genotypes, there was a marked reduction in the amount of pollen shed on the stigma at the high temperature. Pollen germination in the cultivar IET4658 was reduced under the 38/27 C temperature regime. Percentage fertility was positively correlated with the amount of pollen on the stigma at 38/27 C. The large amount of pollen on the stigma in tolerant genotypes appeared to compensate for reduced pollen growth under high temperature. Observations of pollen shedding under field conditions corresponded well with the phytotron results.